Physical Activity Promotion in Healthcare Settings: A Survey in Europe (Baltic Journal of Sport and Health Sciences, 2026)
Background: Physical inactivity is a major contributor to non-communicable diseases in Europe. Although supportive policies exist, there is limited evidence on how physical activity promotion is implemented in healthcare settings across the Region. Objectives: This study aimed to explore how healthcare professionals in various healthcare settings deliver and engage with PA promotion across national and regional levels within the European Region.Methods: A descriptive cross-sectional survey was conducted across 27 EU member states and the United Kingdom, targeting healthcare professionals involved in PA promotion. The survey included quantitative and open-ended items and was distributed online via national representatives.Results: A total of 240 valid responses from 23 countries were analysed. The results revealed substantial heterogeneity in the implementation of the programmes, with scores ranging from 46% (Romania) to 100% (Latvia). The study identified 118 at the national and 68 at the regional level PA programmes, with Slovenia, Lithuania, and the Netherlands reporting the highest numbers. Physicians and physiotherapists were the most involved professionals, and the most frequently reported activity across professions was consultation.Conclusion: This first-of-its-kind survey provides critical insights into the state of PA promotion in European healthcare. The findings highlight regional disparities and the need for more consistent integration of PA strategies into routine care.Keywords: Physical activity, HEPA, healthcare settings, non-communicable diseases, Europe